The Algorithmic Nephrologist: Can AI Predict Chronic Kidney Disease Progression? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Introduction: The Silent Epidemic and the Promise of AI Chronic Kidney Disease (CKD) is a global health crisis, often referred to as a "silent epidemic"...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning